Rictor Activates Cav 1 Through the Akt Signaling Pathway to Inhibit the Apoptosis of Gastric Cancer Cells - Cao, Rui-zhen; Min, Li; Liu, Si; Tian, Ru-yue; Jiang, Hai-yan; Liu, Juan; Shao, Lin-lin; Cheng, Rui; Zhu, Sheng-tao; Guo, Shui-long; Li, Peng (Frontiers in Oncology, 2021)
Background: Rapamycin-insensitive companion of mammalian target of rapamycin (Rictor) protein is a core subunit of mammalian target of rapamycin complex 2, and is associated with cancer progression. However, the biological function of Rictor in cancer, particularly its clinical relevance in gastric cancer (GC) remains largely unknown. Methods: Rictor expression and its association with clinicopathologic characteristics in GC were analyzed by immunohistochemistry. Effect of Rictor and Caveolin-1 (Cav 1) on GC cells apoptosis was evaluated via overexpression experiment in vitro. Mechanisms of Rictor and Cav 1 in GC were explored through overexpression and knockdown, by immunofluorescence and western blot analyses. Results: Rictor was upregulated in GC, and mainly located in the cytoplasm of cancer cells. Moreover, higher Rictor levels were associated with worse prognosis. Rictor could inhibit GC cell apoptosis and promote cell growth in vitro. The results of immunofluorescence revealed that Cav 1 localized in GC cell membrane but did not co-localize with Rictor. Further, Rictor regulated apoptosis-related proteins, long non-coding RNAs and also activated cellular signaling, thereby positively regulating Cav 1 expression. This effect was attenuated by the Akt inhibitor ly294002. Cav 1 did not significantly affect the ability of Rictor to inhibit tumor cell apoptosis. Conclusions: Rictor is upregulated in GC and associated with worse prognosis. It inhibits tumor apoptosis and activates Cav 1 through the Akt signaling pathway to inhibit the apoptosis of GC cells. Rictor is, therefore, a promising prognostic biomarker and possible therapeutic target in GC patients.